Kabinetsformatie 1977. V.l.n.r. Epem-Brugman, Vondeling, Van Thijn, Ter Beek, Kalk,?, Van den Heuvel, Worrell, Meijer - Morelis, Nick (1977)
Kabinetsformatie 1977. V.l.n.r. Epem-Brugman, Vondeling, Van Thijn, Ter Beek, Kalk,?, Van den Heuvel, Worrell, Meijer.